Toxic trace elements in selected edible rhizomes of medicinal plants using INAA and ICP-MS techniques - Abu Bakar, Mohd Daran; Kamaludin, Rashid; Halijah, Ibrahim; Mahanom, Jalil; Yusmin, Mohd Yusof; Shamrulazhar, Shamzir Kamal; Shahril, Efzueni; Reza, Farzinebrahimi (2017)
Consumption the crop is one of the main sources of dietary exposure to toxic trace elements. In order to assess the level of toxic trace elements from selected herbs and to make an assumption on their consumption level of concern, fourteen elements in Zingiber zerumbet(lempoyang), Boesenbergia rotunda (temu kunci), Zingiber officinale var rubrum (halia bara) and Zingiber officinale roscoe (halia) have been determined via ICP-MS (Cd, Be, Ti, Pb) and INAA (As, Al, Ba, Cr, Co, Sb, Sr, Th, U and V) methods. It was revealed that the concentrations of these elements in most selected rhizomes did not exceed the standard dangerous toxic level. However, 47% cadmium accumulationa was detected in Zingiber officinale var rubrum grown in poly-bags.